New records of Antarctic lichens - Passo, Alfredo (2015)
Recent collections from King George Island, Deception Island and the Antarctic Peninsula provide evidence of the presence of previously unrecorded lichen taxa in the Antarctic flora. Parmelia sulcata, previously cited for South Georgia, and Usnea neuropogonoides are recorded for the first time from maritime Antarctica. The distributions of Psoroma buchananii and U. acromelana are extended to theAntarctic Peninsula and to Deception Island, respectively. The taxonomic position of an abnormal form of U. aurantiaco-atra is discussed.